Lipid Profile Parameters and Coronary Artery Disease in Young Patients Undergoing Diagnostic Angiography - Jayaram, Ashwal Adamane; Nayak, Krishnanada; Rao, Sudhakar; Samanth, Jyothi; Kvellur, Sneha T; Saleel, Adamya; Almalki, Yasir; Gajiwala, Nirlip (International Journal of Cardiovascular Practice, 2019)
Introduction: It is vital to understand the association between lipid profile and the severity of coronary artery disease (CAD) in young patients with suspected CAD. The clinical presentation, lipid profile and severity of CAD may differ in patients who develop CAD at young age and those at older age. Friesinger (FR) index is an important tool to assess the extent and severity of coronary artery lesions.Methods: This study was a single center retrospective study involving patients below 40 years who underwent diagnostic coronary angiography. Demographic variables, lipid profile and FR index were estimated. Patients were divided into four groups based on the FR index scores of 0, 1?4, 5?10 and 11-15, respectively.Results: A total of 158 patients (Mean ± SD of age; 35.65 ± 3.81 years) were included in the study. Among demographic variables, gender (P = 0.03) and body mass index (BMI) (P < 0.001) were found to be associated with FR index. In addition, total cholesterol (P < 0.001), low density cholesterol (LDL) cholesterol (P < 0.001), non-high density cholesterol (non-HDL) (P < 0.001) and ratio of triglycerides (TG) /non-HDL cholesterol (P = 0.004) showed significant differences between the FR groups. Logistic regression analysis showed that only diabetes (P = 0.02) and BMI (P = 0.004) were significant predictors of the extent and severity of coronary artery lesions in terms of FR index.Conclusions: A strong direct relationship was observed between total cholesterol, LDL and non HDL cholesterol while a negative correlation with the TG/non HDL ratio. Diabetes and BMI also play a very significant role.